The aggregation effect of organic matter on bauxite residue particles and its improvement mechanism - Dong, Mengyang; Wang, Guizhen; Gul Wazir, Zafran; Liu, Jing; Hou, Guoqin; Gao, Xinyu; Chao, Liang; Rong, Fangxu; Xu, Yuzhi; Li, Mingyue; Liu, Kai; Liu, Aiju; et al. (Frontiers in Environmental Science, 2023)
The utilization rate of bauxite residue is less than 10% due to its high salinity, high alkalinity, low nutrient content and poor physical structure. At present, soil amelioration of bauxite residue is the most promising method for large-scale ecological disposal. In this study, pot culture experiment was conducted to study the effect of organic amendment on the stability of bauxite residue aggregates. The results showed that the physical and chemical properties were improved, and the pH, EC and ESP were reduced to 9.26, 0.61 mS/cm and 55.5%, respectively. Secondly, the fertility level of bauxite residue was greatly improved, and the organic matter content increased to 66.51 mg/kg. With the improvement of environmental conditions, the microbial activity in bauxite residue was greatly enhanced along with the recovery of microbial community structure. At the end of incubation experiment, the value of MWD (mean weight diameter) value of bauxite residues’ particles increased to 0.73 mm, and new lamination structure appears in aggregates. Combined the result of iron and aluminum oxides analysis, it conjectures that microbial community recovery and organic-inorganic complex formation facilitated the fine particles’ aggregation of bauxite residues. Therefore, organic amendment was more implication in soil amelioration of bauxite residues other than the directive modifications on alkalinity.